Ascorbic acid-mediated selenium nanoparticles as potential antihyperuricemic, antioxidant, anticoagulant, and thrombolytic agents - Siddique, Muhammad Aamir Ramzan; Khan, Muhammad Aslam; Bokhari, Syed Ali Imran; Ismail, Muhammad; Ahmad, Khurshid; Haseeb, Hafiz Abdul; Kayani, Mustafa Mubin; Khan, Suleman; Zahid, Nafeesa; Khan, Sher Bahadar (Green processing and synthesis, 2024)
Selenium (Se) is an important trace element that is involved in controlling oxidative stress and inflammatory disorders. Gouty arthritis is the inflammation and pain within the joints and tissues caused due to the accumulation of monosodium urate (MSU) crystals. This study aimed to investigate the antigout, antioxidant, anticoagulant, and thrombolytic potential of ascorbic acid-mediated Se nanoparticles (A-SeNPs). Different analytical techniques were used to investigate the formation of A-SeNPs. The antigout potential of the nanoparticles was carried out using MSU crystal dissolution, uric acid (UA) degradation assay, and xanthine oxidase inhibition (XOI). A-SeNPs exhibited excellent antihyperurecemic activity in a concentration-dependent manner. It was observed that at the tested concentration of 20 mg·mL , the A-SeNPs demonstrated significant breakage and dissolution of MSU crystals and resulted in UA degradation of 67.76%. Similarly, A-SeNPs resulted in 76% XOI with an excellent IC of 140 µg·mL . Furthermore, considerable antioxidant activity was noted for the A-SeNPs as evaluated with multiple antioxidant assays. Finally, the NPs were found to have significant anticoagulant and thrombolytic potential. Thus, it was concluded that A-SeNPs have potent antihyperuricemic, antioxidant, anticoagulant, and thrombolytic activities, making them an ideal choice for future biomedical applications.